(untitled) (Research, Society and Development, 2021)
The aim of this study is to discuss the importance of food safety and consumer protection when using supermarket carts. This is a literature review in the search for articles carried out in the Virtual Library (Scielo) and CAPES, using descriptors referring to microorganisms, cross contamination, Good Manufacturing Practices, hygiene of supermarket carts, food safety and sanitary inspection. Also, the references of selected articles were consulted in order to identify other studies. The present study is characterized as the objective in an explanatory research that aims to identify factors that determine or contribute to the occurrence of phenomena. As for the design, the research configures a bibliographic study, which is characterized by the study of materials already prepared. Bibliographic research is also used to catalog scientific productions. As for the nature, the study is classified as qualitative, as an analysis is carried out on the written content of the articles, in order to ascertain the main methodologies adopted in the investigated studies. The collection technique is an indirect documentation with document and bibliography, together with qualitative data analysis techniques. The data found contributed to results on evaluations carried out in the food environment and the various pathogens found in different environments. Which refers to direct and indirect questions about contaminations arising from personal hygiene, work environment, animals on site, free market microorganism, hygienic-sanitary conditions, that is, these mentioned requirements contribute to the proliferation of contaminants. Prevention is very important through cleaning and sanitizing environments, equipment and hands. It is concluded that long-term monitoring and training in Good Manufacturing Practices in food establishments is necessary to better achieve standardization and quality control.